Impactos ambientais da urbanização: esforços da pesquisa brasileira e mapeamento e percepção de moradores na cidade de Santarém, Pará - MOURA, Verena Cibele Soares (Universidade Federal do Oeste do Pará, 2021)
Nowadays the world is becoming increasingly urban, being one of the most striking processes in contemporary society. This growing urbanization has triggered impacts that affect the relations between the social and the natural environment. In order to analyze these relationships, the present work is divided into two chapters, where the first deals with a scientometric analysis of studies on environmental impacts resulting from urbanization in Brazil. In the second, a mapping was performed and the perception of the population about environmental impacts present in the urban area of Santarém, Pará, Brazil was evaluated. Both chapters are structured in research article format. In chapter I, a search for articles (scientometric analysis) was performed in the Scielo (Scientific Electronic Library Online), Scopus Database (Elsevier) and Web of Science databases, published from 1971 to 2017. A spatial evolution was verified. Scientific publications were found, and 319 articles were found, published only after 1971. It was found that there was a strong positive relationship between the number of works and the year of publication (r = 0.751; p <0.001). The area of expertise of the most frequent researchers was applied social sciences (n = 88; 28%). The impacted health component that obtained the highest number of articles (n = 63; 20%), naturally, the journals that published the most were also those related to this theme. The southeastern region was the largest holder of articles (n = 107; 33%), as well as the Atlantic Forest as its predominant biome (n = 125; 39%), results that reinforce the need for decentralization of research from major economic centers. and expansion to small and medium sized cities. In Chapter II, the spatialization of impacts was performed through a georeferenced database from field visits, focusing on the main urban environmental impacts. Additionally, interviews were conducted (using a pre-established questionnaire) with the residents, in order to verify their environmental perception, where later analyzes were performed with the aid of R and IRAMUTEQ software. From the residents' perception, it was found that throughout the city of Santarém, significant environmental impacts occur, but the negative ones stood out. The Centro neighborhood has characteristics that differ from the other study neighborhoods, being considered developed in the residents' view, however, also presenting many impacts. Expanding neighborhoods represent deficiencies that exist in many peripheral neighborhoods of Santarém-Pa, especially with regard to infrastructure, solid waste and sewage disposal. It is understood that the improvement of urban environmental quality requires a greater contribution from the government and the residents themselves.